The song of the orphans - Price, Daniel, 1970- (Price, Daniel, 1970- Silvers series, 2017)
"The second book in the genre-bending Silvers series--an io9 "can't miss" sci-fi pick--about six extraordinary people whose fates become intertwined on an Earth far different from our own. The end of the world was just the beginning for Hannah and Amanda Given. Saved from apocalypse by three mysterious beings, the sisters were marked with a silver bracelet and transported to an entirely different Earth--a place where restaurants move through the air like flying saucers and the fabric of time is manipulated by common household appliances. There, the Givens were joined by four other survivors in silver: an acerbic cartoonist, a shy teenage girl, an aloof young Australian, and a troubled ex-prodigy. Hunted by enemies they never knew they had, and afflicted with temporal abilities they never wanted, the sisters and their new companions embarked on a cross-country journey to find the one man who can give them shelter. Now, six months after their tumultuous arrival in New York City, the Silvers find themselves in more trouble than ever. Their new world is dying, and a clan of powerful timebenders believes that killing them is the only way to stop it. The U.S. government has sent its most ruthless spy agency to track and capture them. And a new pair of allies--with their own terrifying abilities--endangers the group from within. But their biggest threat of all may be the people who first saved them: the godlike Pelletiers. They had a reason for bringing the Givens and their friends to this world. And when the Silvers learn the awful truth, nothing will ever be the same"--